Regesten Kaiser Sigismunds (1410-1437), Band 3 Die Urkunden und Briefe aus den Archiven und Bibliotheken West-, Nord- und Ostböhmens - Elbel, Petr (2016)
The volume contains 253 abstracts of 229 Emperor Sigismund's charters and letters or deperdita and 21 medieval forgeries or highly suspect documents attributed to this ruler from the archives of southern Bohemia.